Hubungan Antara Jangka Waktu Pembinaan Dengan Penurunan Gejala-gejala Ketergantungan Narkotika - Haryanto Haryanto; Siti Rahayu Harditono (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 1997)
This study was intended to assess the effectiveness of religious in therapy rehabilitating drug addiction among adolescents in InabahÂ· 1, Pondok Pesantren Suryalaya. Tasikmalaya, West Java. The primary hypotheses was tested by calculating the correlation between durationof therapy and the decrease in drug addiction symptoms, which wasmeasured by